Arthropod pests of horticultural crops in tropical Asia - Muniappan, R. (CABI, 2012)
Covers the main arthropod pests of twenty five major crops in tropical Asia, with photographs of their adult and immature stages, their distribution, biology, disease vectors, symptoms of the damage they cause and their natural enemies. This book is suitable for researchers, and policy makers of entomology, pest control and crop protection